2022
DOI: 10.1038/s41398-022-02236-x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide DNA methylation analysis of whole blood cells derived from patients with GAD and OCD in the Chinese Han population

Abstract: Generalized anxiety disorder (GAD) and obsessive-compulsive disorder (OCD) had high comorbidity and affected more than 44 million people around the world leading to a huge burden on health and economy. Here, we conducted an epigenome-wide DNA methylation study employing 93 patients with GAD, 65 patients with OCD, and 302 health controls, to explore epigenetic alterations associated with the onset and differences of GAD and OCD. We identified multiple differentially methylated positions (DMPs) and regions (DMRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…In supporting our findings, three of our twelve most significant DMPs were found in a recent study comparing people with GAD, or OCD, with healthy controls of Chinese Han origin 49 . These probes map to RABGGTB, MPK8IP3, and ENAH genes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In supporting our findings, three of our twelve most significant DMPs were found in a recent study comparing people with GAD, or OCD, with healthy controls of Chinese Han origin 49 . These probes map to RABGGTB, MPK8IP3, and ENAH genes.…”
Section: Discussionsupporting
confidence: 90%
“…Of the 305 probes identified by our analysis, 241 were annotated to 233 genes based on the Illumina annotation. Gene Ontology (GO) analysis, using the R package missMethyl (49,50), for the same probes did not show any term enriched after multiple test corrections. Of note, five terms from the GO analysis showed a nominal p-value < 0.05 (Supplementary table 5).…”
Section: Epigenome-wide Association Studymentioning
confidence: 97%
“…In supporting our findings, three of our twelve most significant DMPs were found in a recent study comparing people with generalized anxiety disorder (GAD), or OCD, with healthy controls of Chinese Han origin [ 80 ]. These probes map to RABGGTB , MPK8IP3 , and ENAH genes.…”
Section: Discussionsupporting
confidence: 87%
“…Xia et al found that epigenome-wide DNA methylation analysis of whole blood cells showed differential expression of CRT1 among individuals with generalized anxiety disorder (GAD), obsessivecompulsive disorder (OCD), and healthy controls. This suggests that CRT1 may help distinguishing patients from healthy controls or classifying patients with GAD and OCD (Guo et al, 2022). SCRT1 also regulated the conversion from microglia to neurons, which was crucial for nerve system development (Malygina et al, 2021).…”
Section: Discussionmentioning
confidence: 99%